Matriarchal Influence and Spiritual Identity: Exploring Women's Spirituality in Young Sheldon - Geeta; Dr. Amit Kumar (Emerging Trends in Languages, 2025)
The study analyzes the TV series Young Sheldon (2017–2024) through maternal and spiritual feminism. It is a prequel to The Big Bang Theory, set in the 1980s. It is based on a ten-year-old Sheldon’s struggles to adjust to his environment. It aims to examine the study critically, emphasizing the role of his mother and her maternal and spiritual practices through episodes of seasons one to five. The study works on five objectives; Mary’s Character analysis, Generational spirituality, Tension between faith and science, and the intersection of faith and family dynamics. It further works on Women’s spirituality as a source of empowerment and resistance. Data analysis employs a qualitative approach as its research design and an analytical research method. The study's main finding is Mary Cooper’s character in Young Sheldon, which highlights the complex intersection of women’s spirituality, gender roles, and family dynamics. Furthermore, the research underscores how Mary’s compassionate authority shapes Sheldon’s moral and emotional development while reinforcing the broader themes of maternal feminism. Her actions reflect a nuanced blend of devotion, resilience, and intuitive guidance that influences the family’s interactions. The study also notes that Mary’s spiritual grounding serves as a stabilizing force amid ongoing conflicts between logic and belief. Overall, the analysis reveals how her role extends beyond traditional motherhood, representing a deeper expression of identity, care, and personal empowerment within a patriarchal setting.
Keywords: Spiritual feminism; family dynamics; gender; matriarchal influence; spirituality